2014
DOI: 10.1016/j.rbmo.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro culture system for mesenchymal progenitor cells derived from waste human ovarian follicular fluid

Abstract: To characterize different cell populations in the human ovary, morphological and functional characteristics of cell populations collected during routine IVF procedures were studied. Cells obtained from follicular fluid grew in vitro under minimal medium conditions, without growth factor, including leukaemia-inhibiting factor. Morphological analysis revealed a heterogeneous cell population, with cells displaying a fibroblast-like, epithelial-like and also neuron-like features. Morpho-functional characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 44 publications
5
37
0
Order By: Relevance
“…Cell nuclei were stained by Hoechst33258 (Sigma Aldrich, St Luis, MO, USA). Cell membrane was observed highlighting the CD44 expression on the hMSCs surface by immunocytochemistry assay as previously described [52]. Cells were observed by confocal microscopy (obj mag 63×) and all confocal images were elaborated by using ImageJ software to evaluate the CS/TPP NPs uptake in hMSCs.…”
Section: Uptake Studiesmentioning
confidence: 99%
“…Cell nuclei were stained by Hoechst33258 (Sigma Aldrich, St Luis, MO, USA). Cell membrane was observed highlighting the CD44 expression on the hMSCs surface by immunocytochemistry assay as previously described [52]. Cells were observed by confocal microscopy (obj mag 63×) and all confocal images were elaborated by using ImageJ software to evaluate the CS/TPP NPs uptake in hMSCs.…”
Section: Uptake Studiesmentioning
confidence: 99%
“…Feasible presence of human ovarian follicle-derived MSCs was published formerly, and these research findings illuminate previous inquiries (Kossowska-Tomaszczuk et al 2009b;Riva et al 2014). Vimentin, which is a specific protein of cytoskeleton intermediate filaments of mesenchymal cells, was chosen to determine cell populations isolated from human FF (Riva et al 2014). Immunofluorescence showed an intense cytoplasmic staining for vimentin in MSC at different times of culture.…”
Section: Discussionsupporting
confidence: 57%
“…Our observations indicated that this fluid, despite the presence of granulosa and thecal cells (Honda et al 2007;Kossowska-Tomaszczuk et al 2009b), consist of heterogeneous cell populations involving a cell collection exchanging fibroblast-like morphology and other characteristics of MSCs (Kucia et al 2005). Feasible presence of human ovarian follicle-derived MSCs was published formerly, and these research findings illuminate previous inquiries (Kossowska-Tomaszczuk et al 2009b;Riva et al 2014). Vimentin, which is a specific protein of cytoskeleton intermediate filaments of mesenchymal cells, was chosen to determine cell populations isolated from human FF (Riva et al 2014).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations